Mitotic exit in mammalian cells. - Kapuy, O; He, E; Uhlmann, F; Novák, B (2009)
This is an open-access article distributed under the terms of the Creative Commons Attribution Licence, which permits distribution and reproduction in any medium, provided the original author and source are credited. Creation of derivativeworks is permitted but the resultingworkmay be distributed only under the same or similar licence to this one. This licence does not permit commercial exploitation without specific permission. © 2009 EMBO and Macmillan Publishers Limited All rights reserved.